A PESAN MORAL DAN KEMANUSIAAN DALAM REPRESENTASI PENYAKIT BIPOLAR PADA FILM “KUKIRA KAU RUMAH” KARYA UMAY SHAHAB - MELSA NURALISA; NUR AMRULLAH, MUDZHIRA; MATHAR, HASBULLAH (Jurnal Washiyah, 2026)
This study aims to analyze the moral and humanitarian messages as well as the representation of bipolar disorder in the film Kukira Kau Rumah by Umay Shahab. The study uses a qualitative approach with case study methods and Roland Barthes' semiotic analysis (denotation, connotation, and myth). Data were collected through visual observation, scene documentation, and interviews with eight informants. The results of the study indicate that the film contains moral messages about the importance of empathy, social support, self-acceptance, awareness of treatment, and the removal of stigma against mental disorders. The representation of bipolar disorder is depicted through episodes of depression, mania, hypomania, and mixed states that illustrate the emotional dynamics of the main character. Keywords: Moral Messages, Humanity, Bipolar, Representation, Semiotics